RENDEMEN DAN KUALITAS MINYAK ATSIRI EUCALYPTUS PELLITA PADA BERBAGAI WAKTU PENYIMPANAN BAHAN BAKU - Ratnaningsih, Ambar Tri; Insusanty, Enny; Azwin, Azwin (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
Forest harvesting waste in the form of Ecalyptus pellita leaves can be utilized to be essential oil by distillation process. The research aimed to 1) to know the effect of duration of leaf storage on yield and quality of essential oil produced, 2). Comparing the quality of E.pellita leaves essential oil with eucalyptus oil according to SNI. Methods taken by taking E. pellita leaf waste were then stored for 1,2,3,4,5 and 6 days then steam distillation and measured rendemen, specific gravity, sineol content and refractive index. The average oil yield of E.Pellita is 0.15% with the highest yield of 0.4593% in leaves stored for 3 days. The best essential oil quality comes from leaves that have been stored for 3 days with specific gravity of 0.9186, 60% sineol content, refractive index 1.4603 and 80% alcohol solubility by 1: 1.